Significance of CRM for HR Consultants - Nagu, Vinay Kumar (Prabandhan: Indian Journal of Management, 2011)
CRM (Customer Relationship management) is all about the theory used by companies to administer and manage their customers, partners, vendors and other stakeholders efficiently.The more often primary Customer Service KPI is based on mere quantity, the less true Customer Satisfaction is going to take place. The only accurate KPI for Customer Service Performance is the actual perception of the Customer as to whether or not they received adequate service.In Customer Service, the outcome for the Customer and for the Company, is in the hands of the professional Customer Service person. How well they perform in each contact with their Customers depends on a number of factors. Their training will have an impact, as will their knowledge, skills and motivation. One of the strongest influencer on their performance with the Customer will be their ATTITUDE.If you are a Customer Service person, or are building a Team of Customer Service people, it is important that you work at developing the RIGHT attitude, values and beliefs. We all recognize someone with a bad attitude, someone who thinks Customers are stupid, or annoying, or someone who hates their job or their Company. These types of attitudes ensure that these Customer Service people are guaranteed to give their Customers a very bad experience.Identifying the IDEAL Customer Service attitude is important, so that we can build this ideal attitude in ourselves and in our Teams. We call this attitude an Assertive Customer Focussed Attitude.